Wittenberg and Byzantium: Lutheran Incentives to Correspond with the Patriarch of Constantinople (1573–1581). (Journal of Religious History, 2022)
Since the publications of Ernst Benz's Wittenberg und Byzanz (1971) and Dorothea Wendebourg's Reformation und Orthodoxie (1986), the late sixteenth‐century correspondence between the Greek Orthodox Church and Lutheran theologians from Tübingen has become more popular in historical and ecumenical scholarship. Accordingly, this article primarily builds upon the research of Wendebourg, Asaph Ben‐Tov, and Richard A. Calis. arguing that three interlocking incentives drove the Lutherans to engage formally with the Patriarch of Constantinople from 1573 to 1581. First, Lutheran interest began with Martin Luther's polemic with Rome and grew with his comrade Philip Melanchthon. Second, within the context of the unitive efforts of Jakob Andreae and the Formula Concordiae (1577), the Lutheran theologians earnestly sought to promote their theological convictions while equally desiring to gain the Eastern Church as an ally. And finally, the correspondence provided a sub‐context for Martin Crusius, arguably the most important Lutheran correspondent, to advance his knowledge of the Greek language and culture. Crusius's interests, while remaining thoroughly Lutheran, allowed him to keep a cordial disposition throughout, and even beyond, the correspondence. Such an irenical bent was critical to maintaining a line of communication between these two Christian traditions which substantially disagreed on various doctrinal matters.